Perfectly Japanese : - White, Merry Isaacs (University of California Press, 2002)
Are Japanese families in crisis? In this dynamic and substantive study, Merry Isaacs White looks back at two key moments of "family making" in the past hundred years--the Meiji era and postwar period--to see how models for the Japanese family have been constructed. The models had little to do with families of their eras and even less to do with families today, she finds. She vividly portrays the everyday reality of a range of families: young married couples who experience fleeting togetherness until the first child is born; a family separated by job shifts; a family with a grandmother as babysitter; a marriage without children.